Formulation of Logit Regression - Ahmad, Asraf; Sorooshian, Shahryar; Cheng, Jack Kie (Akademi Baru, 2016)
This article is in the form of a short tutorial discussion, presenting the logistic (logit)regression mathematical method. Logistic regression as one of the most popular modeling approach used in the research and decision makings, has its own specialty than other common linear regression method whereby the response variable is discrete and form of S-shaped. The paper starts with the short review of logistic regression method, formulation of the method and finally, authors’ conclusion is the last section of this paper